Оптимальное управление нестационарным тепловым процессом с осевой симметрией - Копец М.М. (Проблемы управления и информатики, 2016)
Розглянуто лінійно-квадратичну задачу оптимального керування нестаціонарним тепловим процесом з осьовою симетрією. Таким способом отримано необхідні умови оптимальності. На основі цих умов виведено інтегро-диференціальне рівняння Ріккаті, розв’язок якого дав можливість виписати явну формулу для обчислення оптимального керуванння. The article is devoted to the linear–quadratic optimal control problem of nonstationary thermal process with axial symmetry. To find the solution of our problem we propose a method of Lagrange multipliers. In this way, we obtain necessary conditions for optimality. On the basis of these conditions it is derived integro-differential Riccati equation whose solution has made it possible to write down explicit formula for the calculation of the optimal control.